LA TERAPIA DE REEMPLAZO ENZIMÁTICO EN EL TRATAMIENTO DE ENFERMEDADES GENÉTICAS - Sáenz, Homero; Instituto de Errores Innatos del Metabolismo. Pontificia Universidad Javeriana, Bogotá (2003)
The aim of enzyme reemplacement therapy (ERT), is to provide a foreign protein to a patient who is producing it abnormally. The protein to be  used may be purified from human fluids or tissues and from bacteria, yeast or mammalian cells in which the corresponding human gene has been introduced. Up to now three diseases are currently being treated worldwide with ERT, Gaucher, Fabry and the combined severe human immunodeficiency. Advanced studies are in progress for the following diseases Hurler, Hunter, Pompe, Niemann-Pick B type, Morquio A,  hereditary angioderma and penfigo vulgar. One of the problems of using ERT is the its high costs, due to both the low number of patients affected world-wide and the very expensive procedures required to obtain protein expression in mammalian cells. To overcome these problems there are two possible alternatives: expression in bacteria or in yeast, however bacteria do not glycosylate proteins and most of inborn errors of  metabolism are caused by deficiency in glycosilated proteins (GP).  Yeast glycosilate proteins, but they have different pattern of   glycosylation from mammalian